(3OQGSI aj GdbGfhf GdeOfj hGdebGQfs - (3YGeQ bGSe CMeO(B, (3GdbjSjs ((3YeGf(B;(3OGQ GdKbGaI ddfTQ(B:s (3GdOGQ GdYdejI(B,s, 2002)
(3MeGjI GdeSJgdc aj Xd GdeHGOF GdJbdjOjI(B:(3YQV MeGjI GdeSJgdc, eMGhdI JWhjQ MeGjI GdeSJgdc, bUhQ GdMeGjI aj Xd GdeHGOF GdJbdjOjI , MeGjI GdeSJgdc aj Xd eHGOF eYGUQI(B:(3GdeHGOF GdYGeIdMeGjI GdeSJgdc, MeGjI GdeSJgdc aj fWGb GSJNOGe GdefJLGJ hGdNOeGJ, JhXja GdELQGAGJ GdbGfhfjI dMeGjI GdeSJgdcs
(3HHdhZQGajG U(B.250s
Keywords: (3GdGSJgdGcs; (3GdbGfhfs; (3MeGjI GdeSJgdcs